Test kresby rodiny ako indikátor rodinnej ideológie - Monika Sirkovská (AntropoWebzin, 2011)
Author in the contribution devote to research of authority and subordination in the family from the perspective of visual anthropology. Everyday family life is controlled by a set of culturally specific values and norms that determine the appropriate family ideology. Research of the family dynamics can provide the basic image of the various forms of relationships. Author realized research of power manifestations in the mountain village at the north of Slovakia which is characterized by frequent occurrence of the patriarchal family. The authority in the patriarchal family ideology is attributed to older men belonging to the paternal lineage; it is typically associated with patrilineality, patrilocality and focusing on ancestors. The question is how can we explore the subjective perception of authority in the case of children. It seems to be very helpful to apply the special projective technique – the family drawing test. Aim of this contribution is to show not only interface between theoretical concepts and practical collection of empirical data in the field, but also the interpretation of specific children's drawings. End-of-conference, author would like to highlight that anthropologist has to detect the specific socio-cultural environment of studied families, because its knowledge plays the key role in the complex interpretation of visual material.